ChemInform Abstract: Trifluoromethanesulfonic Acid Catalyzed Friedel—Crafts Alkylations of 1, 2, 4‐Trimethoxybenzene with Aldehydes or Benzylic Alcohols. Issue 37 (22nd August 2013) - Wilsdorf, Michael; Leichnitz, Daniel; Reissig, Hans‐Ulrich
Abstract An operationally simple and mild protocol for double arylation of aldehydes and for substitutions of benzylic alcohols is developed.